Fahr’s Syndrome- An Interesting Case Presentation - Asokan, Athulya Geetha (JCDR Research and Publications (P) Limited, 2013)
Fahr’s syndrome refers to a rare syndrome which is characterized by symmetrical and bilateral intracranial calcification. We are presenting a 63 year old male, who complained of progressive dysarthria of 6 months, which was associated with slowness of movements. His neurological examination revealed Parkinsonian features. His CT scan revealed a symmetrical large area of calcification over the basal ganglia, the thalamus and the cerebellum. The secondary causes of the bilateral calcification were ruled out to make the clinical diagnosis of Idiopathic Bilateral Striopallidodentate Calcinosis, which is otherwise called as the Fahr’s syndrome. Deposits of calcium and minerals cannot be linked to a single chromosomal locus and further genetic studies are in progress for identifying the chromosomal locus of the disease.